TRADISI TONJOKAN PADA UPACARA PERNIKAHAN DI DESA AJUNG WETAN KABUPATEN JEMBER JAWA TIMUR DALAM PERSPEKTIF KOMUNIKASI - Betari Chintya; Redi Panuju (Prodi Ilmu Komunikasi Universitas Putera Batam, 2021)
Marriage is one of human needs in life. In Indonesia wedding ceremony has various traditions that have been carried out from generation to generation. As found in the Ajung, Jember, East Java. The tradition carried out in the village of Ajung Wetan Jember is quite unique. They invite the neighbourhood to the wedding within food, cigarette or soap. This kind of tradition is known as tradisi tonjokan. From that uniqueness, the writer chose tradisi tonjokan as topic of this research to explore more deeply, how the villagers interpret these traditions within symbolic interaction perspective in communication studies. Authors used a qualitative as a research method . Data were collected by in-depth interview and observe the Ajung residents. The result of this research is that the villagers of Ajung Wetan Jember interpret the tradisi tonjokan as a way of inviting close relatives or neighbors using soap, cigarettes, or food. Furthermore, what is unique about this tradition from Ajung Wetan Jember is the items used to invite, side dishes of rice, cigarettes, and soap. The last, the tradisi tonjokan has another purpose besides inviting, that is a respect and gratitude for the person who is invited. Also on the other hand, tradisi tonjokan is considered as obligation to attend the wedding ceremony.